What can we learn from the implementation of monetary and macroprudential policies: a systematic literature review - Lubis, Alexander; Alexiou, Constantinos; Nellis, Joseph G. (Wiley, 2019)
The emergence of macroprudential policies, implemented by central banks as a means of promoting financial stability, has raised many questions regarding the interaction between monetary and macroprudential policies. Given the limited number of studies available, this paper sheds light on this issue by providing a critical and systematic review of the literature. To this end, we divide the theoretical and empirical studies into two broad channels of borrowers - consisting of the cost of funds and the collateral constraint - and financial intermediaries - consisting of risk-taking and payment systems. In spite of the existing ambiguity surrounding coordination issues between monetary and macroprudential policies, it is argued that monetary policy alone is not sufficient to maintain macroeconomic and financial stability. Hence, macroprudential policies are needed to supplement monetary. Additionally, we find that the role of the exchange rate is critical in the implementation of monetary and macroprudential policies in emerging markets, whilst volatile capital flows pose another challenge. In so far as how the arrangement of monetary and macroprudential policies varies across countries, key theoretical and policy implications have been identified.
Keywords: monetary policy; macroprudential policy; capital flows; payment system; exchange rate; systematic literature review